Integration of off shore wind generation in the regional ASEAN grid - Bhargava Ankit. (2012)
The development of off wind farms in the ASEAN region may be utilized in the development of the ASEAN grid for the benefit of the entire ASEAN region. There are several proposed ASEAN Grid networks. In the long term, incorporating off shore wind generation can be utilized with much benefit.